Penggunaan Media Kliping Berbasis Model Pembelajaran Kontekstual pada Mata Pelajaran IPAS untuk Meningkatkan Kreativitas Siswa - Fauziah, Riska; Sulistiani, Sulistiani; Maharani, Nyimas Desinta Aish; Ardiansyah, Muhammad; Sani, Muhammad Anwar (STKIP HARAPAN BIMA, 2026)
This study aims to determine the improvement of students' creativity through the use of clipping media based on a contextual learning model in the social science (IPAS) subject on climate and its changes in fourth grade at SDN 27 Ampenan. The method used is classroom action research (CAR) on fourth-grade students totaling 22 students who were given treatment using clipping media based on the contextual learning model. The instruments used were observation instruments. Data collection techniques involved using tests. Data analysis was conducted by comparing students' initial and final behaviors. Based on the data analysis obtained at the pre-stage, the assessment scale was low, then at the post-stage, the students received a very good assessment scale. The results of the study indicate that the use of clipping media based on the contextual learning model can improve the creativity of fourth-grade students at SDN 27 Ampenan in the social science (IPAS) subject on climate and its changes.